Criminal behavior – Ayurvedic perspective - M, Thasni; M, Jithesh (International Research Journal of Ayurveda & Yoga, 2021)
Crime is an intentional commission of an act usually deemed socially harmful or dangerous and specifically defined, prohibited, and punishable under criminal law. It is unquestionably one of the prevailing and worrying aspect in most of the societies. Criminal behaviour is often a difficult topic to discuss, as there are different variables that must be taken into account in order to truly define and obtain a thorough understanding of the concept. It is often a matter of debate whether the criminals are born bad or made bad. The born traits alone do not inevitably lead to crime and the circumstances do not make criminals of everyone; but together they create a population responsible for a large fraction of crimes. The intentions and attitude of indulging into criminal behaviour is dominated by the personality, attitude, physiology, learning, motivation, thinking and other cognitive factors. In, Ayurveda the criminality can be explained under the concept of Prajnaparadha. In Prajnaparadha we do things without discriminating as to whether an action is favourable or harmful. Ayurveda have directly and indirectly discussed the concepts of criminal behaviour in various contexts like Anna Raksha Adhyaya, Dashavidha Papa karma etc. Hints about the evolutionary aspects of deviant behaviors are discussed in the context where Charaka discusses 3 types of Satvas – Deva, Manusha and Pashu. The born behavioral patterns are further explained in the context where Saatvikadi prakrithi is explained. Chandogyopanishad and Bhagavath Geetha also provides references regarding the role of Ahara and the behavioral patterns. Ayurveda also explains the psychopathological causation of crime under the context of Unmada. Ayurveda offers a number of practical and powerfully effective tools for balancing common disturbances of the mental and emotional realm. This paper makes a humble effort to discuss the different aspects of criminal behavior, the primary, secondary and tertiary preventive strategies and rehabilitation along with the parallel concepts in Ayurveda.